COST ANALYSIS OF WATER RESOURCES MANAGEMENT SERVICES BELANTI II IRRIGATION AREA CENTRAL KALIMANTAN PROVINCE - Dozier, Alpha; Oetomo, Wateno; Wulandari, Esti (Transpublika Publisher, 2022)
The Belanti II Swamp Irrigation Area in Pulang Pisau Regency, Central Kalimantan, spans 3,275 Ha. Water management activities, necessitated for sustained irrigation, incur the Water Resources Management Service Fee (BJPSDA), calculated on cost recovery principles. This study aims to (1) Determine the BJPSDA value by considering the economic benefit factor, (2) Assess farmers' Ability To Pay (ATP) and Willingness To Pay (WTP) for BJPSDA, and (3) Evaluate the Belanti II swamp irrigation network and optimization efforts. The BJPSDA in Belanti II is Rp5,625,504,000, with agricultural benefits contributing Rp51,468,721,052.40 (51.86% of NME). The cost is Rp570,151.69/Ha or Rp101/m3. Farmer ATP and WTP for BJPSDA are Rp54/m3. The irrigation system lacks proper water flow regulation structures, but optimization efforts include channel normalization and water control structures. To enhance leaching ability, 500 m3/ha/day of fresh water is needed. Structures like weirs and flap gates regulate water supply during high and low tides, respectively. These initiatives aim to ensure consistent irrigation and sustainable water resource management in Belanti II.